PERAN MEDIASI KOMITMEN ORGANISASI PADA PENGARUH KOMPETENSI TERHADAP KEPUASAN KERJA DI PT. XYZ - STEFANIE RHINDY ATMAVIA; DENTA FELLI ANANDA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This study aims to analyze the mediating role of organizational commitment on the influence of self-competenceand ethics on job satisfaction at PT. XYZ. The research sample consisted of 94 permanent employees of PT. XYZ, selected using a purposive sampling technique based on criteria of at least 2 years of work experience, age over 22 years, and being permanent employees of specific directorates, particularly the Human Capital division. Data was collected through online questionnaires using a Likert scale. Based on the results of the hypothesis test data analysis, this study shows several findings: self-competence influences organizational commitment, self-competence influences job satisfaction, organizational commitment influences job satisfaction, and ethical competence influences organizational commitment. However, there is no direct influence of ethical competence on job satisfaction. Furthermore, organizational commitment is proven to mediate the influence of self-competence on job satisfaction and also mediates the influence of ethical competence on job satisfaction.